Lower limb joint kinetics in the sprint start push-off - Charalambous, L.; Irwin, G.; Bezodis, I.; Kerwin, D.; Harle, R. (ISBS - Conference Proceedings Archive (Konstanz), 2009)
Previous studies have analysed lower limb joint kinetics during sprint performance, but not addressed the earliest contact out of the blocks. The aim of this study was to report lower limb joint moments and powers during the first stance phase of the sprint push-off. One competitive male sprinter performed 10 maximal sprint starts. An automatic motion analysis system (CODA, 200 Hz) with synchronised force plate data (1000 Hz) were used to collect kinematic profiles at the hip, knee and ankle and ground reaction forces for the first stance phase. Cluster markers defined the orientation of the lower limb segments in 3D. Knee and hip kinetics differed to the later phases of sprint, whereas similarities were found at the ankle. This study highlights the need for the push-off phase to be considered separately from both research and practical perspectives.